Inducing Neuro-linguistic changes in human brain to improve the efficiency of human being - Shobanbabu, RJ; Raju; Kumar Chengali, Anil (International Journal of Computer Sciences and Engineering, 2025)
The potential of the right brain like Intuition, Creativity, Sensitivity can be achieved by the generation of Alpha & delta waves in the human brain. It helps human beings to be efficient in their physical, mental & spiritual welfare & helps the human beings in day to day life to be healthy, lovable, intuitive, emotional balance, creative & make them a better decision maker. It is the technique of fine tuning the frequency of our thoughts to the most subtle frequency. This can be achieved by the change of the Neurological setup in the brain by making the neuron to fire & wire each other making them to communicating with each other. Change in the Neurological setup can be achieved by the practicing the Heartfulness meditation, exercises to increase the ability of brain to regenerate neurons, left and right brain synchronization exercises, exposure to Brain waves oscillation, music to enhance brain connections, eyeball exercises to enhance the neuronal circuits & by activities for sensory augmentation.